Population and Sample as Methodological Basis in Educational Research - Hasfiana; Syarifuddin Ondeng; Ulfiani Rahman (Penerbit Hellow Pustaka, 2026)
Population and sampling are fundamental methodological components that determine the validity, reliability, and generalizability of educational research findings. Inadequate determination of population boundaries, inappropriate sampling techniques, or improper sample size selection may lead to biased conclusions and weaken the scientific credibility of research outcomes. This study aims to critically examine the concepts of population and sample as methodological foundations in educational research. Employing a qualitative descriptive approach through library research, this study analyzes and synthesizes relevant methodological literature and scholarly articles using content analysis techniques. The findings indicate that population serves as the basis for defining the scope of research generalization, while samples function as representative subsets selected through systematic procedures. Effective sampling requires careful consideration of sample size adequacy, sampling techniques, population characteristics, and desired levels of precision and confidence. The study also highlights fundamental differences in sampling practices between quantitative and qualitative research paradigms, where quantitative research emphasizes statistical representativeness, whereas qualitative research prioritizes data saturation and contextual depth. This article contributes to methodological discourse by providing a systematic conceptual clarification of population and sampling frameworks, particularly for novice researchers in education. A comprehensive understanding of these concepts is essential to designing rigorous, credible, and impactful educational research.